The struggle for power and its impact on Hafsid Africa (675-772 AH / 1276-1370 AD) - Ahmed, Maryam Miloud Saad (Tobruk University Journal of Social and Human Sciences, 2022)
The title of this research is the struggle for power and its impact on Hafsid Africa. Princely councils and private councils. In the third topic, we discussed external influences and their impact on scientific and cultural life in Africa during this period, with a focus on the Moroccan influence due to the Marinid control over Ifriqiya during that period, in addition to clarifying that influence on the field of architecture and the arts as well.